KESESUAIAN KOMPETENSI KEAHLIAN LULUSAN SEKOLAH MENENGAH KEJURUAN (SMK) DENGAN KOMPETENSI KERJA DUNIA USAHA DAN INDUSTRI (DU/DI) DALAM BIDANG KEAHLIAN TEKNIK KOMPUTER JARINGAN (TKJ) DI KABUPATEN CIREBON - Arifudin S.T.,M.Kom (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2019)
This study aimed to know: 1)the suitability of student competence in conventional school between business field and industry (DU/DI) 2) To know the competence which was needed DUDI toward Conventional School. 3) To know range of suitability graduate student competence in Conventional School with DUDI. 4) To know the standardization of facilities and infrastructure as required by DUDI. This study used descriptive method by using survey. The object of this study wasstudents in Conventional School which had selected in TKJ’s program in Cirebon Regency. Based on the finding data, there were found several things as follows: 1) Competence SMK’s graduate in the field of expertise TKJ were still not absorbed in DUDI. 2) School facilities and infrastructure were still inadequate for the effectiveness of student learning. 3) Teachers were still had lack experience in DUDI especially in the work process. 4) The school was still not followed DUDI development in Computer and Network field. The result of this studywascompetenceof SMK’s graduates in TKJ was reached 81,95 The required level of competence DUDI reaches 66%, the level of standardization of infrastructure facilities in the school against DUDI reached 61.11%.